2020
DOI: 10.1097/sla.0000000000003850
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Reliable Surgical Quality Assurance System for 2-stage Esophagectomy in Randomized Controlled Trials

Abstract: Objective: The aim was to develop a reliable surgical quality assurance system for 2-stage esophagectomy. This development was conducted during the pilot phase of the multicenter ROMIO trial, collaborating with international experts. Summary of Background Data:There is evidence that the quality of surgical performance in randomized controlled trials influences clinical outcomes, quality of lymphadenectomy and loco-regional recurrence. Methods: Standardization of 2-stage esophagectomy was based on structured ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Future studies, both observational cohort studies and randomized controlled trials, must seek to address this, with pictures or videos at the end of the lymphadenectomy providing an accurate measurement of intraoperative findings as well as a measure of quality of surgery and lymphadenectomy. 35 This study had important limitations. First, a clear treatment selection bias existed between the patients receiving esophagectomy and those receiving gastrectomy, with surgeon preference often an unmeasured but crucial driving factor.…”
Section: Discussionmentioning
confidence: 93%
“…Future studies, both observational cohort studies and randomized controlled trials, must seek to address this, with pictures or videos at the end of the lymphadenectomy providing an accurate measurement of intraoperative findings as well as a measure of quality of surgery and lymphadenectomy. 35 This study had important limitations. First, a clear treatment selection bias existed between the patients receiving esophagectomy and those receiving gastrectomy, with surgeon preference often an unmeasured but crucial driving factor.…”
Section: Discussionmentioning
confidence: 93%
“…Of these, 137 full-text articles were assessed for eligibility with a final inclusion of 44 studies in our qualitative synthesis (see Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B108). 15–58 For 39 of these studies, sufficient details on the variance components were reported or obtained from the authors for the quantitative synthesis (meta-analysis). 15–27,29–43,45,47–52,54,56–58…”
Section: Resultsmentioning
confidence: 99%
“…The surgical techniques were quite different from those in the last century. As the only local control method in NAC combination, surgical QC should be stricter 28 . In the 8911 trial, there was no MIE, and the surgical experience was limited compared to that currently 2 .…”
Section: Discussionmentioning
confidence: 99%